Huellas de la sociedad musulmana granadina: la conversión del Albayzín (1499-1500) - Carrasco García, Gonzalo (En la España Medieval, 2007)
The mass baptism of Muslims in Granada at the turn of the sixteenth century was one of the key events that marked the end of an era. These religious conversions have been studied with the use of a series of baptismal lists from the central parishes of the Albaicín district. The issues related to this event, which took place in the span of a few days, are laid out in order to grasp the logic of the conversions. Furthermore, the data provided by these lists allows us to sketch a sociological portrait of the Muslim community with issues ranging from family structure, trades, and the various minority groups including Elches, Blacks, slaves and Mudejars. This study allows us to retrieve the vestiges of Nasrid society after the Christian conquest and the absorption of Granada by Castile.